Modelling the Dynamics of Crime Against Women by Incorporating Role of Technology - Shelly Khurana; , Anil Kumar Nishad; Sushant Shekhar (Indian Journal of Forensic Medicine and Pathology, 2025)
that, despite attempts, remains a substantial challenge. It can have serious and long-term consequences for their physical, emotional, and psychological well being. Technology can help combat crime against women by providing tools and resources for preventing, reporting, and dealing with abuse and harassment. Aim: To combat crime against women in India and create a safe environment for them. Objectives: To investigate the effectiveness of technology in lowering crime against women. Material: A nonlinear mathematical model has been constructed taking into account five interacting variables namely, targeted, susceptible, criminals, victims, and technology. Result: Our model shows the presence of two equilibria: crime-free and crime persistent. The crime-free equilibria (CFE) always exist, while crime-persistent equilibria (CPE) exist when criminality reproduction number ( 0 c 0 c R ) is greater than 1. Further, stability analysis has been carried out. Analysis demonstrated that when R >1, crime-persistent equilibria is nonlinearly asymptotically stable under some restrictions on parameters. The impact of key parameters on the dynamics of crime against women is also investigated through numerical simulation. Conclusion: According to the model study, the use of technology like installing Safetipin or another emergency app, addressing areas with poor safety, introducing wearable tech etc can effectively minimize crime against women in society